PERANCANGAN APLIKASI PENYISIPAN PESAN MELALUI METODE MIXING (PARITY CODING DAN ENKRIPSI ADVANCED ENCRYPTION STANDARD/AES) PADA FILE MP3 - Fuad, Raja Nasrul (Jurnal TIMES, 2021)
One of the encoding techniques is steganography as a way of hiding secret messages/files on the media as a container in a certain way so that no one knows or realizes that there is a secret message/file, while in cryptographic techniques the original message you want to send (plaintext) is changed or encrypted. with a key into a meaningless random information (ciphertext), because it is random, a suspicion arises of the message sent. The advantages of Steganography and Cryptography in data security so that through this study, two data security techniques were combined using the Parity Coding method for steganography and the AES (Advanced Encryption Standard) algorithm. In this study, the carrier or cover file proposed is an mp3 file, while the secret message/file to be inserted in the carrier is in the form of various types of txt formats.